TEMPO catalyzed oxidative dehydrogenation of hydrazobenzenes to azobenzenes. Issue 18 (22nd April 2020) - Lv, Haiping; Laishram, Ronibala Devi; Yang, Yong; Li, Jiayan; Xu, Dandan; Zhan, Yong; Luo, Yang; Su, Zhimin; More, Sagar; Fan, Baomin
Abstract : A metal-free direct oxidative dehydrogenation approach for the synthesis of azobenzenes from hydrazobenzenes has been developed by using TEMPO as an organocatalyst for the first time. Abstract : A metal-free direct oxidative dehydrogenation approach for the synthesis of azobenzenes from hydrazobenzenes has been developed by using TEMPO as an organocatalyst for the first time. The reaction proceeded in open air under mild reaction conditions. A wide range of hydrazobenzenes readily undergo dehydrogenation to give the corresponding azobenzenes in excellent yields.